1972
DOI: 10.1111/j.1365-2672.1972.tb03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Glucose by Torulopsis glabrata Occurring Naturally in the Stomachs of Newborn Animals

Abstract: Summary: The elucidation of the mechanism of ethanol production in the stomachs of newborn animals is described. The condition was reproduced in lambs and piglets by feeding glucose in fat‐free milk, and shown to arise from fermentation by the naturally occurring yeast Torulopsis glabrata, which can reach population densities of 106 viable cells/ml of stomach contents. These yeasts ferment glucose, producing up to 500 mg of ethanol/100 ml of contents in the stomach, but do not ferment sucrose or lactose. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The first two of these were always fermented with the production of ethanol ( Table 2). These coliform bacteria are similar to the organisms described but not identified earlier (White et al 1972) from the stomach content of lambs. They are now known to be regularly motile at 22 O C and their ability to ferment sucrose may be absent or delayed.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The first two of these were always fermented with the production of ethanol ( Table 2). These coliform bacteria are similar to the organisms described but not identified earlier (White et al 1972) from the stomach content of lambs. They are now known to be regularly motile at 22 O C and their ability to ferment sucrose may be absent or delayed.…”
Section: Resultssupporting
confidence: 83%
“…Sampling of rumen contents, culturing techniques, media and ethanol estimations by gas liquid chromatography were all as described elsewhere (White et al 1972;White 1977). The coliform organisms were therefore all isolated in a medium at pH 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…There do not, however, appear to be any data on levels of ethanol in the human portal vein. Further evidence of the effect of microbial ethanol production has been obtained, where high levels of ethanol in the blood of lambs, piglets and calves fed on milk substitutes were associated with high numbers of Torulopsis yeasts in the stomach (White et al 1972;White 1974). These authors, using GLC, demonstrated up to 500 mg/100 ml ethanol in the stomach, and levels of 300-500 mg/l00 ml of ethanol in plasma from the recurrent tarsal vein or jugular vein of lambs.…”
Section: A Chemical Methodsmentioning
confidence: 99%
“…This yeast was shown to reach population densities of lo6 viable organisms/ml of stomach contents and .to produce up to 500 mg of ethano1/100 ml of contents. Torulopsis glabrata is also known to be a common inhabitant of the human digestive tract and it has been suggested as a cause for endocarditis, Lees et al (1971) and Wickerham (1957).…”
Section: Resultsmentioning
confidence: 99%
“…Torulopsis ylabrata and perhaps other Torulopsis yeasts have been identified as common inhabitants of neonatal animal stomachs (White et al 1972). These yeasts have also been established as common inhabitants of the human digestive tract and have been implicated in a few human infections (Wickerham 1957;Lees et al 1971). In addition, Abe et aI.…”
mentioning
confidence: 99%